PENGARUH PAJAK DAN RASIO PROFITABILITAS TERHADAP TRANSFER PRICING - Kinta Putri Yuwanda (2023)
This research is using quantitative study aimed to see whether there are influence of taxes and profitability ratios on transfer pricing. This study uses 20 mining companies in the energy sector that have been listed on the Indonesia Stock Exchange (IDX) as samples. The sample selection used a purposive sampling method, an acceptable sample is 26.4% of the total number of mining companies in the energy sector. Testing the hypothesis in this was used Multiple Linear Regression Analysis using SPSS analysis tool with a significant level of 0.05 %. The results of these tests indicate that (1) there is no (significant) influence of taxes on transfer pricing and (2) there is no (significant) influence of profitability ratios on transfer pricing.